2021
DOI: 10.3390/s21248214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Recliner Chair with Rocking Motions on Sleep Efficiency

Abstract: In this study, we analyze the effect of a recliner chair with rocking motions on sleep quality of naps using automated sleep scoring and spindle detection models. The quality of sleep corresponding to the two rocking motions was measured quantitatively and qualitatively. For the quantitative evaluation, we conducted a sleep parameter analysis based on the results of the estimated sleep stages obtained on the brainwave and spindle estimation, and a sleep survey assessment from the participants was analyzed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 113 publications
(146 reference statements)
1
3
0
Order By: Relevance
“…In parallel, Baek et al's exploration of rocking movements during three-hour naps in 15 young patients showed similarities to our findings, particularly regarding the increased duration of deep sleep (N3) and a significant reduction in the N1 stage (p < 0.005). The decreased latency period to enter deep sleep and the heightened frequency of sleep spindles align with our results, supporting the notion that rocking motions positively impact the sleep transition process [24].…”
Section: Discussionsupporting
confidence: 90%
“…In parallel, Baek et al's exploration of rocking movements during three-hour naps in 15 young patients showed similarities to our findings, particularly regarding the increased duration of deep sleep (N3) and a significant reduction in the N1 stage (p < 0.005). The decreased latency period to enter deep sleep and the heightened frequency of sleep spindles align with our results, supporting the notion that rocking motions positively impact the sleep transition process [24].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, compared to a stationary condition, continuous rocking (at 0.25 Hz) during an afternoon nap or the night promoted sleep by reducing latency into and maintenance of deep sleep (non-REM) in healthy volunteers [108,109]. Finally, a study evaluating the effects of a recliner chair with a rocking motion on sleep in healthy volunteers reported a decrease in light sleep and an increase in deep sleep when the chair moved compared to being stationary [110].…”
Section: Perspective Of Using Vestibular Stimulation To Improve Sleep...mentioning
confidence: 98%
“…The study by Ashida et al [33] was excluded as it measured the subjectively perceived effectiveness of the sleep-inducing effect without recording sleep EEG. Three further studies were discarded [34][35][36] since they did not use the minimum number of electrodes for each recommended region (i.e., frontal, central, and occipital) that are necessary to score sleep according to AASM criteria. Moreover, in the study by Muto et al [34], participants triggered the rocking condition themselves, leading to a lack of blinding and possibly to placebo effects.…”
Section: Studiesmentioning
confidence: 99%